Sagot :
Step-by-step explanation:
To evaluate the function for
f(−3)
we need to substitute −3
for every occurrence of x
and then evaluate the results:
f(x)=x2+1
becomes:
f(−3)=−32+1
f(−3)=9+1
f(−3)=10
Answer:
substitute
−3
for every occurrence of x and then evaluate the results:
f(x)=x2+1
becomes:
f(−3)=−32+1
f(−3)=−32+1f(−3)=9+1
f(−3)=−32+1f(−3)=9+1
f(−3)=−32+1f(−3)=9+1 f(−3)=10
Step-by-step explanation:
sa pic nalang po kayo tumingin mas maayos
HOPE ITS HELP
#CARRY ON LEARNING
#BETTER WITH BRAINLY
![View image Andreivenz0907](https://ph-static.z-dn.net/files/dbe/846bb58240154e3993f0ed5832473595.jpg)